Quality approach to the sustainability of public transport - Susnienė, Dalia (Transport, 2012)
Transport is an essential part of national economic, social and sustainable development that can produce both positive and negative effects on the environment and the quality of life depending on the level of development and indicated preferences. Modern interpretations of sustainable urban development require reducing the use of private cars through improving the quality of public transport services. Therefore, identifying the inefficiencies of the public transport system will help with improving service management, expanding coverage and increasing the attractiveness of public transport services. There is a general agreement that excellent customer service is a source of competitive advantage. The key to providing effective customer service is the accurate determination of the customer's needs and response to them in a consistent manner in order to assure their satisfaction. The SERQUAL model was employed as an instrument to measure customer satisfaction and give valuable information and guidelines for transport service companies on necessary improvements in their daily operations. The SERQUAL approach, in case service quality is defined and measured as the difference between expectations and perceptions, is the major point of departure from the previous attempts to find possible solutions to improving public transport services.First Published Online: 30 Mar 2012